STATUS OF POTATO SEED SYSTEMS IN SOUTH WEST ASIA (SWA) - Kadian, M S; Ilangantileke, S.; Arif, M.; Hossain, M.; Roder, A; Sakha, B. M.; Singh, S. V; Farooq, K.; Mazeen, A. C. M (Potato Journal, 2013)
Potato is an important food and cash crop in seven countries of South and West Asia (SWA). The SWA region produces about 32.8 million tones of potato from an area of 1.95 million hectares. In the region, India is the largest potato producer, followed by Bangladesh, Pakistan, Nepal, Afghanistan, Sri Lanka and Bhutan. The constraints to enhance potato production in the region are similar but are agro-ecology and country specific. The shortage of quality seed is one of the major limiting factors to increase productivity. The improved technologies for quality seed production are available but are not being implemented judiciously. Most of the countries in the region except India import seed to meet the domestic seed requirement. They do not have sufficient infrastructure, resources and trained manpower to produce required quantities of formal seed. The seed is the most expensive input for potato cultivation and sometimes it accounts up to 60%. The seed systems in India are well established but some of the areas do not get sufficient quality seed. In this paper, the seed production systems and future strategy to develop sustainable seed program of the seven countries of SWA region are presented.